Abdominal injuries caused by a horse kick - rescue procedure - Marcin Leśkiewicz; Rafał Czyż (Kazimierz Wielki University, 2018)
Kicking by the horse can cause very serious injuries to the victim. The groups of people particularly vulnerable to such an injury are: veterinarians, farmers, sport riders and stables. The aim of this article is to present the proceedings with the victim, who was kicked by a horse with special attention to abdominal injuries. Injuries caused as a result of horse kick are paradoxically quite frequent. Early call for help, precise gathering of the interview according to the SAMPLE algorithm and patient's observation in the direction of shock symptoms may later help the ambulance crew and emergency medicine physician in treatment and in faster, targeted diagnostics in the emergency department.